INTERSTELLAR TRAVEL purpose and motivations. (ELSEVIER, 2023)
Interstellar Travel: Purpose and Motivations is a comprehensive, technical look at the necessary considerations for interstellar travel addressed by leading experts in the field, from scientists studying possible destinations (exoplanets) and the vast distances between, to those concerned with building institutions and capabilities in society that could sustain such endeavors. In addition to the technical, medical, and anthropological aspects of deep space travel, the ethics and morality of spreading Earth-based life to other worlds is also examined. In the first book of a three-book compilation, Interstellar Travel: Purpose and Motivations offers in-depth, up-to-date and realistic technical and scientific considerations in the pursuit of interstellar travel and is an integral reference for scientists, engineers, researchers and academics working on, or interested in, space development and space technologies. With a renewed interest in space exploration and development evidenced by the rise of the commercial space sector and various governments now planning to send humans back to the moon and to Mars, so also is interest in taking the next steps beyond the Solar System and to the ultimate destination - planets circling other stars.